2017
DOI: 10.1530/rep-17-0328
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones regulate sperm–oviduct interactions in the bovine

Abstract: After insemination in the cow, a sperm reservoir is formed within the oviducts, allowing the storage and then progressive release of spermatozoa toward the ovulated oocyte. In order to investigate the hormonal regulation of these events , the ovarian steroids 17β-estradiol (E2) and progesterone (P4) were added at various concentrations to monolayers of bovine oviduct epithelial cells (BOEC) before or during co-incubation with spermatozoa. Main findings demonstrate that (1) a 18-h pretreatment of BOEC with 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 55 publications
0
66
0
Order By: Relevance
“…In addition, previous studies suggest that seminal estrogen has a positive effect on sperm transport and fertilization and is also responsible for rapid sperm elimination from the uterus through the cervix in the pig 71 . It has also been reported that sperm binding to the oviductal cells is triggered by high concentrations of estrogen within the oviduct 72,73 . Interestingly, the SP-P1 group showed an overrepresentation of the Estrogen signaling pathway in our study.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, previous studies suggest that seminal estrogen has a positive effect on sperm transport and fertilization and is also responsible for rapid sperm elimination from the uterus through the cervix in the pig 71 . It has also been reported that sperm binding to the oviductal cells is triggered by high concentrations of estrogen within the oviduct 72,73 . Interestingly, the SP-P1 group showed an overrepresentation of the Estrogen signaling pathway in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Once sperm reach the utero-tubal junction, sperm will be trapped and released progressively to reach the oocyte at the fertilization site. The use of an in vitro model of bovine oviduct epithelial cells (BOECs) cultured as monolayers showed that sperm bind spontaneously to the cells and are released by progesterone and that sperm that have been bound to BOECs and released by progesterone action displayed a higher fertilization potential than those of the control (Lamy et al, 2017). A comparative proteomic analysis of bound v. control sperm showed that a total of 27 proteins are captured by the sperm (Lamy et al, 2018).…”
Section: Fertilizationmentioning
confidence: 99%
“…Spermatozoa incubated with OF or SP + OF also showed the myosin heavy chain 9, a protein previously described in human spermatozoa, where it plays a role in oviductin binding to the sperm surface [ 91 ]. Lamy et al [ 92 ] suggested the formation of a complex between myosin heavy chain 9 and two other proteins, oviductin and actin cytoplasmic 1, involved in modulating the capacitation process. Another protein, cofilin-1, was detected in the OF and SP + OF groups, and it is a protein that participates in sperm capacitation, inducing the acrosome reaction, as shown in humans [ 93 ].…”
Section: Discussionmentioning
confidence: 99%